1998
DOI: 10.1074/jbc.273.35.22640
|View full text |Cite
|
Sign up to set email alerts
|

Expression Cloning of Human Corneodesmosin Proves Its Identity with the Product of the S Gene and Allows Improved Characterization of Its Processing during Keratinocyte Differentiation

Abstract: In human epidermis and other cornified squamous epithelia, corneodesmosin is located in the desmosomes of the upper living layers, and in related structures of the cornified layers, the corneodesmosomes. During maturation of the cornified layers, the protein undergoes a series of cleavages, thought to be a prerequisite of desquamation. Partial amino acid sequencing of corneodesmosin fragments suggested that it is related to the product of the S gene, previously identified in the human major histocompatibility … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
59
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 55 publications
(62 citation statements)
references
References 33 publications
3
59
0
Order By: Relevance
“…5B and data not shown). Moreover, the transcripts of corneodesmosin, which encode a putative adhesion glycoprotein thought to play a key role in the function of corneodesmosomes and thus in corneocyte cohesion (Guerrin et al, 1998), were fourfold lower in mutant than control skin (Fig. 5C).…”
Section: Ablation Of Brg1 In Keratinocytes Of the Forming Epidermis Imentioning
confidence: 99%
“…5B and data not shown). Moreover, the transcripts of corneodesmosin, which encode a putative adhesion glycoprotein thought to play a key role in the function of corneodesmosomes and thus in corneocyte cohesion (Guerrin et al, 1998), were fourfold lower in mutant than control skin (Fig. 5C).…”
Section: Ablation Of Brg1 In Keratinocytes Of the Forming Epidermis Imentioning
confidence: 99%
“…Immunohistochemistry was performed using two monoclonal antibodies to Cdsn, G36-19 and F28-27 (Serre et al, 1991), which label different epitopes in the central domain of the Cdsn protein (Guerrin et al, 1998). Five-micron-thick sections were mounted on glass slides and either fixed in acetone (frozen tissue) or dewaxed in xylene and alcohol and microwave pretreated (paraffin-embedded tissue).…”
Section: Allen Et Almentioning
confidence: 99%
“…Some desmosomal proteins are important in maintaining keratinocyte cell-cell adhesion, and it is likely that Cdsn forms part of the adhesive network (Serre et al, 1991). Cdsn has a high glycine content, which implies a potential to form adhesive loop structures at the cell surface, as seen with other epidermal proteins (Guerrin et al, 1998). Progressive proteolytic digestion of Cdsn has been proposed, which would account for the decrease in molecular size between the stratum granulosum and stratum corneum, and the gradual reduction and eventual loss of adhesive function with associated scale formation.…”
mentioning
confidence: 99%
“…Cloning of its encoding cDNA revealed that CDSN is located on chromosome 6, in PSORS1, the major locus for psoriasis susceptibility. The mRNA encodes a 529-amino acid protein with a N-terminal signal peptide and one putative Nglycosylation site, consistent with the demonstration that it is secreted and glycosylated [7].…”
Section: Cdsn: Discovery Of a New Protein Specific To The Late Steps mentioning
confidence: 67%